Relationship between functional hamstring: quadriceps ratios and running economy in highly trained and recreational female runners - Sundby, Ø. H.; Gorelick, M. L. S. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to investigate the relationship between running economy (RE), functional hamstring:quadriceps peak torque ratios (f-H:Q), and flexibility among female runners. Seven highly trained (HT) female runners (age: 25.7 ± 4.7 years, VO2peak of 62.0 ± 4.8 ml/kg/min) and 11 recreational female runners (age of 28.8 ± 5.6 years, VO2peak of 49.2 ± 4.6 ml/kg/min) were measured for maximal aerobic power (VO2peak), RE, heart rate, respiratory exchange ratio, f-H:Q (Hecc:Qcon and Hcon:Qecc), and sit-and-reach hamstring/trunk flexibility. On 2 separate days, RE was measured on a treadmill at 1% grade at 2 velocities (160.9 and 201.2 m/min) for 6 minutes each, and isokinetic knee strength was measured at 3 angular velocities (60, 120, and 180°/s) for both concentric and eccentric muscle actions. The unpaired t-tests showed a consistent trend toward higher f-H:Q ratios at all angular velocities among the HT runners. Highly trained runners had significantly higher Hecc:Qcon at 120°/s (p < 0.05) and 180°/s (p < 0.05). Whole group correlations demonstrated a significant correlation between Hcon:Qecc at 180°/s and RE (ml·kg/0.75km) at 201.2 m/min (R = -0.48, p < 0.05). No significant relationships were found between flexibility, or hamstring and quadriceps peak torque (N·m) and RE (p > 0.05). This cross-sectional analysis suggests that higher f-H:Q torque ratios, and not muscle strength per se, are associated with a lower metabolic cost of running. Therefore, runners should consider implementing hamstring exercises to improve their f-H:Q ratios.